Post-marketing safety surveillance and re-evaluaiton of Shu-Xue-Ning injection: a real-world study based on 30,122 cases - Xinyao, Jin; Yifan, Zhang; Keyi, Wang; Wentai, Pang; Chunyang, Wang; Hui, Wang; Chunxiang, Liu; Yunhua, Xue; Wenke, Zheng (Frontiers in Pharmacology, 2023)
Objective: This study aims to investigate the safety of Shu-Xue-Ning injection (SXNI) in real-world clinical applications. Methods: A prospective, multi-center, large-sample intensive monitoring method was used to monitor the use of SXNI in several medical institutions across China while collecting patients’ dosing and adverse event information. Patients who suspected as adverse reactions made comparisons with patients who did not report adverse reactions to calculate the correlation between relevant risk factors and suspected adverse reactions. Statistical analysis software SAS 9.1 was used for data analysis. Results: A total of 48 hospitals participated in this intensive monitoring study of SXNI, and 30,122 patients were monitored from July 2015 to December 2018. A total of 1,908 adverse events were reported during the use of SXNI, with an adverse event rate of 6.33% and a 95% confidence interval (CI) of 6.06–6.61%. Association assessment showed that 54 cases presented with SXNI-related adverse reactions with an incidence of 0.18% and a 95% CI of 0.13–0.23%, thereby indicating that the incidence of SXNI-related adverse reactions was occasional. SXNI-related adverse reactions involved 9 systems-organs with 20 clinical manifestations, and the most common adverse reactions were rash, pruritus, and other damages of skin and its appendages. No serious adverse reactions were observed; 27.78% of the adverse reactions occurred within 30 min of drug administration and more than half of them occurred within 2 h of drug administration; 96.3% of the adverse reactions were cured or improved. Causal analysis showed that women, long dispensing time, short medication course and slow dripping speed rate were considered as risk factors. Conclusion: The incidence of SXNI-related adverse reactions in real-world clinical applications is occasional and in a reasonable range with a good prognosis.